2019
DOI: 10.3390/nano9111598
|View full text |Cite
|
Sign up to set email alerts
|

Bias Tunable Photocurrent in Metal-Insulator-Semiconductor Heterostructures with Photoresponse Enhanced by Carbon Nanotubes

Abstract: Metal-insulator-semiconductor-insulator-metal (MISIM) heterostructures, with rectifying current-voltage characteristics and photosensitivity in the visible and near-infrared spectra, are fabricated and studied. It is shown that the photocurrent can be enhanced by adding a multi-walled carbon nanotube film in the contact region to achieve a responsivity higher than 100 mA W−1 under incandescent light of 0.1 mW cm−2. The optoelectrical characteristics of the MISIM heterostructures are investigated at lower and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 63 publications
0
31
0
Order By: Relevance
“…The narrowing of the depletion region allowed the electrons to tunnel easily in the left MS, resulting in the enhancement of photoconductive gain under DUV illumination. In addition, the band model of the Schottky barrier with the forward and reverse bias has been clearly described and proposed by Bartolomeo et al, which can be found in Reference [92].…”
Section: Deep-ultraviolet Photodetectorsmentioning
confidence: 99%
“…The narrowing of the depletion region allowed the electrons to tunnel easily in the left MS, resulting in the enhancement of photoconductive gain under DUV illumination. In addition, the band model of the Schottky barrier with the forward and reverse bias has been clearly described and proposed by Bartolomeo et al, which can be found in Reference [92].…”
Section: Deep-ultraviolet Photodetectorsmentioning
confidence: 99%
“…to account for the rectifying electrical characteristics observed in field effect transistors with ultrathin transition‐metal dichalcogenide channel [ 6,7 ] or in metal/insulator/semiconductor structures. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…CNTs have attracted particular attention due to the ease of production through multiple methods and the possibility to achieve both metallic and semiconducting NTs, depending on their chirality and diameter. [ 4–9 ] However, the difficulty in selecting the desired CNT properties during the production process, commonly leading to a mixture of metallic and semiconducting CNTs in the final product, makes their use in technological applications an open challenge. In recent years, inorganic layered materials, such as MoS 2, [ 10–13 ] PdSe 2, [ 14–16 ] WSe, [ 17,18 ] WS 2 , [ 19 ] and GeAs [ 20 ] have been widely studied for their unique electrical and optical properties.…”
Section: Introductionmentioning
confidence: 99%